1982
DOI: 10.1254/jjp.32.299
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the antiulcer drug geranylgeranylacetone on aspirin-induced gastric ulcers in rats.

Abstract: Abstract-Antiulcer effects of geranylgeranylacetone (GGA) on aspirin induced gastric ulcers in rats were studied, comparing them with those of gefarnate. The oral administration of GGA prevented the development of gastric ulcer induced by a single or repeated oral administration (5 consecutive days) of aspirin. The effects of GGA were more potent and more definite than those of gefarnate. The intraduodenal administration of GGA, but not the intragastrical administration, also inhibited the ulceration induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 12 publications
(9 reference statements)
2
18
0
Order By: Relevance
“…Azuumi et al (20) also reported that aspirin reduced gastric mucosal glycoprotein content prior to the macroscopic lesion formation, and they suggested that aspirin-induced mucosal lesions were caused by the reduction of gastric mucus. Murakami et al (21) and Oketani et al (22) examined the effect of teprenone on the amount of gas tric mucus in aspirin-treated rats, and conse quently they speculated that teprenone inhib ited aspirin-induced mucosal lesions by pre venting the reduction of gastric mucus, parti cularly of macromolecular glycoproteins. In the present study, KB-5492, as well as tepre none, significantly inhibited both the macro scopic lesion formation and the reduction of mucosal hexosamine content induced by aspi rin.…”
Section: Discussionmentioning
confidence: 99%
“…Azuumi et al (20) also reported that aspirin reduced gastric mucosal glycoprotein content prior to the macroscopic lesion formation, and they suggested that aspirin-induced mucosal lesions were caused by the reduction of gastric mucus. Murakami et al (21) and Oketani et al (22) examined the effect of teprenone on the amount of gas tric mucus in aspirin-treated rats, and conse quently they speculated that teprenone inhib ited aspirin-induced mucosal lesions by pre venting the reduction of gastric mucus, parti cularly of macromolecular glycoproteins. In the present study, KB-5492, as well as tepre none, significantly inhibited both the macro scopic lesion formation and the reduction of mucosal hexosamine content induced by aspi rin.…”
Section: Discussionmentioning
confidence: 99%
“…Tetraprenylacetone (TPA: teprenon, geranylgeranylacetone) is a novel anti-ulcer agent developed in Japan (1,2). It is reported that this drug has the ability to protect gastric mucosa against damaging-agents such as ethanol (ET) without inhibition of gastric acid secretion (3).…”
mentioning
confidence: 99%
“…Murakami et al (12) demonstrated that teprenone, an anti-ulcer agent known to enhance gastric mucosal defen sive factors, prevented the aspirin-induced gastric mu cosal lesions in pylorus-ligated rats at 100 and 200 mg/kg, i.d. Terano et al (13) have reported that intra venous teprenone (200 and 400 mg/kg) prevented the aspirin-induced decrease in PD in rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, teprenone did not affect the aspirin-in duced decrease in PD even at the anti-ulcer dose of 200 mg/kg, i.d. (12). Since teprenone was administered i.d.…”
Section: Discussionmentioning
confidence: 99%